The guidance website: Internet strategy implementation at the university in industrial 4.0 content - Ananda, Rusydi; Rafida, Tien; Mardhatillah (International Journal of Innovative Research and Scientific Studies, 2023)
Guidance and counseling are the processes of providing assistance to individuals or groups of individuals at every age stage so that the supervisor can understand and direct himself in accordance with the societal norms and the individual feels happy and effective in his behavior and builds his welfare. This study was carried out with the goals of developing web-based social media advice, implementing guidance web pages, overcoming obstacles and developing students' potential. The ADDIE development research technique was used for data analysis. According to the findings of internet-based online media about university assistance, the study sample consists of eighty different students enrolled at the university in North Sumatra and twelve students use the internet as a tutoring service. The students can easily use the website to solve the issues that they faced and it should be accessible to them at all times.